Angle-of-attack and Mach number effects on the aeroacoustics of an SD7003 airfoil at Reynolds number 60, 000. Issue 1 (March 2023) - Vittal-Shenoy, Dhanush; Gojon, Romain; Jardin, Thierry; Jacob, Marc C.
The aeroacoustics of an SD7003 airfoil at Reynolds number 60, 000 is investigated using Large Eddy Simulation. Five simulations are performed to study the effects of angle-of-attack and Mach number at fixed Reynolds number. For the three cases with angle-of-attack equal to 0° (M = 0.1, 0.3 and 0.6), a pure tonal noise associated with a 2D organisation of the flow is obtained. This flow topology is due to the establishment of a well known aeroacoustic feedback loop between the separation point on the suction side of the airfoil and the trailing edge. The occurrence of this loop is corroborated by the presence of a standing wave pattern with characteristic mode number in accordance with Panda's model. The main effect of the Mach number is to promote flow separation and hence increase separation length and mode number. In addition, the first harmonic and the sub-harmonic of the tone, observed in the far field acoustic spectrum, are found to be generated in the wake, presumably due to non-linear vortex interactions. For the two other angles-of-attack 4° and 8° at M = 0.1, the feedback loop does not establish and a Laminar Separation Bubble (LSB) is observed. When increasing the angle-of-attack, the LSB shrinks with earlier reattachment. For those two cases, far-field spectra are characterized by a low frequency associated with the breathing motion of the LSB and the reattachment point fluctuating in space. The frequency of this fluctuation depends on the curvature of the bubble. Far-field spectra are also characterized by a broadband trailing edge noise whose frequency range decreases with the angle-of-attack. Again, this evolution is found to depend on the curvature of the bubble which may promote a centrifugal instability in the separated shear layer.